Principles of Anatomy and Physiology. - Tortora, Gerard J.; Derrickson, Bryan; Tortora, Gerard J. (Hoboken, N.J. : Wiley, 2006)
The art and illustration program and the innovative learning features make the explanations and concepts of anatomy and physiology easier to understand in this 11th edition of 'Principles of Anatomy and Physiology'.
Partial contents: A brief atlas of the skeleton, surface anatomy, and selected medical images / Gerard J. Tortora.
Previous ed.: 2002.
Includes index.
Internet access card in front pocket.
Text on lining paper.
Keywords: Human anatomy; Human physiology; Health and Wellbeing